Immobilized enzyme as well as biological oil preparation method and device based on reusable enzyme
Immobilized enzymes were solved by preparing the Immobilized enzymes by using polyethylene glycol-modified Fe3O4 nanoparticle carrier in a heterogeneous sludge mixing system and burying them in sodium alginate gel microspheres. The problem of difficulty in reusing and easy to breakage has significantly improved the stability and reusability of enzymes and achieved an efficient bio-oil production process.
Patent Information
- Application Number
- CN202510060929.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-15
AI Technical Summary
In the prior art, immobilized enzymes are difficult to reuse in heterogeneous sludge mixing systems, and are prone to shattering during stirring, resulting in serious loss of enzyme activity and significantly reduced half-life.
Using polyethylene glycol-modified Fe3O4 nanoparticles as matrix, immobilized enzymes were prepared by ultrasonic dispersion and stirring and adsorption in ultrapure water, and they were dispersed in aqueous sodium alginate solution with the second part of free protease, and passed through Ca2+ Ion hardening and glutaraldehyde cross-linking reactions form reticular large pore size gel microspheres, embedding immobilized enzymes to improve their stability and reusability.
It significantly improves the stability and reusability of immobilized enzymes in heterogeneous sludge mixing systems, extends the half-life of the enzyme, reduces shear damage to immobilized enzymes, and realizes sludge/immobilized enzymes and oils. /In-situ separation of water.
Smart Images

Figure CN119464269A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an immobilized enzyme, and a bio-oil production method and a device based on the reusable use of the enzyme. Background Art
[0002] One of the bottlenecks limiting the large-scale application of aqueous enzymatic extraction of tea seed oil is the high price of biocatalytic enzymes and their difficulty in reuse. Therefore, it is an inevitable choice to use immobilized enzymes instead of free enzymes. After the enzyme is immobilized, it has good environmental tolerance and stronger stability, and the enzyme activity can be continuously maintained after repeated use, and it is easy to recycle. However, immobilized enzymes are mostly used in homogeneous liquid systems, and there are few reports on heterogeneous systems where pulp and residue coexist. On the one hand, it is difficult to separate the immobilized enzyme from the solid reactant in the heterogeneous system, and the immobilized enzyme cannot be reused; on the other hand, due to the presence of particulate reactants, the solid particles and the immobilized enzyme collide and rub for a long time during the stirring and mass transfer process, resulting in the breakage of the immobilized enzyme, and the enzyme is released into the solution, which causes a serious loss of activity of the immobilized enzyme and a significant reduction in the half-life.
[0003] The immobilized enzyme carrier is highly rigid and more easily broken. The immobilized catalysts commonly used are prepared by surface adsorption of diatomaceous earth and ion exchange resins. Although they are highly active, the frequent collisions with particulate materials during the stirring process cause the enzyme to separate from the carrier and dissolve into the solution, which quickly inactivates it and cannot be recovered. At present, the most effective way to recover immobilized enzymes in mixed solutions is to magnetize the immobilized enzymes. In addition, there is a lack of bioreactors specifically used for bio-enzymatic oil production from oilseeds, and the stirring blades of traditional reactors cause great damage to immobilized enzymes. In addition, traditional reactors cannot achieve simultaneous separation of in-situ immobilized enzyme / slurry and oil / water to achieve continuous hydrolysis of oilseeds. Summary of the invention
[0004] In view of the above technical problems existing in the prior art, the object of the present invention is to provide an immobilized enzyme, and a bio-oil production method and device based on the reusable enzyme.
[0005] The technical solution adopted by the present invention is as follows: A method for preparing an immobilized enzyme, which comprises using polyethylene glycol-modified Fe 3 O 4 The nanoparticles are used as a matrix, and the matrix and the first part of free protease are stirred in ultrapure water to allow the free protease to be fully adsorbed on the matrix, and then filtered, the nanoparticles are collected and freeze-dried to obtain polyethylene glycol-modified nanoFe 3 O 4 The immobilized protease is loaded, and then dispersed in the sodium alginate aqueous solution together with the second part of free protease and mixed evenly, so that the sodium alginate is coated on the outer layer, and then sequentially passed through the Ca 2+The two-step process of ion hardening and glutaraldehyde cross-linking reaction makes the outer layer of sodium alginate react to form a mesh-like large-pore gel microsphere, and the polyethylene glycol-modified nano-Fe 3 O 4 The immobilized protease and the second part of free protease are co-embedded in the gel microspheres, and finally washed with distilled water and vacuum freeze-dried to prepare the second part of free protease and polyethylene glycol-modified nano-Fe 3 O 4 The preparation of the microsphere complex loaded with immobilized protease is completed.
[0006] Furthermore, the polyethylene glycol modified nano-Fe 3 O 4 The preparation method of the loaded immobilized protease specifically comprises the following steps: Step 1: Fe 3 O 4 The nanoparticles are dispersed in a polyethylene glycol aqueous solution, and the suspension is ultrasonically dispersed at 30-50°C for 10-30 minutes under nitrogen flow, and the precipitate is collected by centrifugation and freeze-dried to obtain polyethylene glycol-modified nano-iron oxide; wherein the molecular weight of the polyethylene glycol is 500-2000, Fe 3 O 4 The mass ratio of nanoparticles to polyethylene glycol is 1:1.5-1.8; Step 2: The polyethylene glycol-modified nano-iron oxide obtained in step 1 and the first part of free protease are dispersed in ultrapure water at a mass ratio of 4-8:1, and the adsorption is stirred for 10-30 minutes under the condition of adjusting the pH to 7.5-8.5, and then filtered, the nanoparticles are collected and freeze-dried to obtain the polyethylene glycol-modified nano-Fe 3 O 4 Loading of immobilized protease.
[0007] Furthermore, the second portion of free protease and polyethylene glycol-modified nano-Fe 3 O 4 The method for preparing a microsphere complex loaded with immobilized protease specifically comprises the following steps: S1: Polyethylene glycol modified nano-Fe 3 O 4 The immobilized protease and the second part of free protease are dispersed in a sodium alginate aqueous solution at a mass ratio of 0.8-1.2:1, wherein the polyethylene glycol-modified nano-Fe 3 O 4 The mass ratio of the loaded immobilized protease to sodium alginate is 1:1.5-3; S2: The mixed solution obtained in step S1 is sprayed into Ca 2+After hardening treatment in an ionic aqueous solution at 2-5°C for 0.5-2h, magnetic immobilized microspheres are obtained, which are washed with distilled water; wherein the sodium alginate in step S1 and the Ca in step S2 2+ The mass ratio of ions is 1:0.3-0.5; S3: The magnetic immobilized microspheres obtained in step S2 are immersed in an excess of 0.1-1% mass dispersion of glutaraldehyde aqueous solution, and a cross-linking reaction is carried out at room temperature for 1-2 hours. The precipitate is then separated by centrifugation, washed with distilled water to remove excess glutaraldehyde, and then vacuum freeze-dried to complete the preparation.
[0008] A bio-oil production method based on reusable immobilized enzymes comprises the following steps: adding shelled camellia seed powder and soft water into a stirred reactor, adjusting the pH value of the reaction solution to alkaline, adding the immobilized enzyme prepared by the invention, and carrying out a stirring hydrolysis reaction; after the reaction is finished, stopping the stirring, standing to allow oil and water to separate into layers, discharging the upper layer of grease, and obtaining product oil after dehydration and drying; then restarting the stirring, electrifying the annular magnet on the outer side of the stirred reactor, allowing the immobilized enzyme to be adsorbed on the inner wall of the side of the stirred reactor, discharging the mixed solution containing pulp residue from the lower discharge port at the bottom of the stirred reactor, and after flushing the inside of the stirred reactor with clean water, re-adding the shelled camellia seed powder and soft water to carry out the next batch of hydrolysis reactions, thereby realizing the reusability of the immobilized enzymes.
[0009] Furthermore, the mass ratio of the shelled camellia seed powder to soft water for the hydrolysis reaction is 1:4-10, and the mass of the immobilized enzyme is 0.5-1% of the mass of the shelled camellia seed powder.
[0010] Furthermore, the reaction temperature for the hydrolysis reaction is 50-70°C, the reaction time is 3-5h, and the stirring speed is 150-300rpm.
[0011] Furthermore, during the hydrolysis, the pH of the reaction solution is adjusted to 8.5-9.5.
[0012] The device used in the bio-oil production method described in the present invention comprises a stirred reactor of a kettle structure, an overflow port is arranged at the upper end of the stirred reactor, a lower discharge port is arranged at the bottom, a heat exchange jacket for heating the stirred reactor is arranged on the outside of the stirred reactor, a heat exchange fluid is passed into the heat exchange jacket, an annular magnet is arranged on the side of the heat exchange jacket, and the annular magnet is connected to the power supply through a wire, and the stirred reactor and the heat exchange jacket are both made of non-magnetic stainless steel; a stirring paddle is arranged at the center of the stirred reactor, the upper end of the stirring paddle passes through the top of the stirred reactor and is fixedly connected to the motor, and a plurality of groups of stirring blades are arranged at intervals from top to bottom at the lower end of the stirring paddle, for example, 2-10 groups of stirring blades can be arranged, and each group of stirring blades includes 3-4 stirring blades evenly spaced along the circumference. The edge of the stirring blade is a smooth arc edge, the stirring blade is inclined relative to the horizontal plane, and the stirring blade is evenly distributed with liquid permeable holes. The stirring blade of the present invention can achieve efficient mixing during stirring, reduce fluid resistance and shear damage to the immobilized enzyme. The stirring paddle and the stirring blade are both made of plastic.
[0013] Furthermore, the stirring paddle and the stirring blades are both made of polytetrafluoroethylene.
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1) The stability and in-situ separation convenience of the immobilized enzyme in the heterogeneous slurry-residue mixing system of the present invention are greatly improved, and the immobilized enzyme can be better reused. In addition, the stirring blade of the bio-oil reactor is improved, and the stirring blade can achieve efficient mixing during stirring, reduce fluid resistance and shear damage to the immobilized enzyme, and further improve the stability of the immobilized enzyme.
[0015] 2) The immobilized enzyme developed by the present invention is combined with the device used in the bio-oil production method of the present application to facilitate the in-situ separation of pulp / immobilized enzyme and oil / water, while better protecting the immobilized enzyme and effectively extending its half-life. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a schematic diagram of the structure of the device used in the bio-oil production method of the present invention.
[0017] Figure 2 It is a schematic diagram of the structure of the stirring blades on the stirring paddle.
[0018] Figure 3 The present invention is applied to Example 1 of the present invention, and the stirred reactor designed by the present invention is used to carry out the hydrolysis reaction. When the immobilized enzymes are respectively prepared by Examples 1 to 6, the oil yield corresponds to the total hydrolysis time under the number of times the immobilized enzyme is used.
[0019] Figure 4In Application Example 2 of the present invention, a conventional reactor is used to carry out hydrolysis reaction. When the immobilized enzymes are prepared in Examples 1 to 6, the oil yield is plotted against the total hydrolysis time at the times the immobilized enzymes are used. DETAILED DESCRIPTION
[0020] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0021] The alkaline protease used in the examples of the present invention is a liquid alkaline protease purchased from Novozymes (China) Biotechnology Co., Ltd., with an activity of 280800 U / g.
[0022] The method for determining the activity of proteases is based on GB / T 23527-2009: 1 mL of appropriately diluted enzyme solution is reacted with 1 mL of 1 g / mL casein solution in a constant temperature water bath at 60°C for 10 min, 2 mL of 0.4 mol / L trichloroacetic acid solution is added to terminate the reaction, and then the mixture is allowed to stand for 10 min to precipitate unhydrolyzed casein, and the supernatant is filtered out using filter paper. Casein is used as a substrate, and the catalytic activity of the supernatant is determined by the Folin method. Take 1 mL of the supernatant and mix it with 5 mL of Na 2 CO 3 Solution (0.4 mol / L) and 1 mL of Folin phenol reagent diluted 3 times with deionized water were mixed, kept at 40°C for 20 minutes for color development, and the absorbance was measured at 680 nm. The enzyme solution in which trichloroacetic acid was first added to terminate the reaction was used as a blank control, that is, trichloroacetic acid solution was first added to the enzyme solution, and then casein solution was added. The protease activity was determined by treating the standard enzyme solution under the same experimental settings with known activity. One unit (U) of protease activity is defined as the amount of enzyme required to hydrolyze casein to release 1 μmol of tyrosine per minute.
[0023] Blank Example 1 Nano-Fe 3 O 4 The preparation method was solvent thermal reduction method, specifically: 162 g FeCl 3 , 90 g trisodium citrate and 540 g sodium acetate were dispersed in 9 L ethylene glycol and stirred for 30 min. The mixed solution was transferred to an autoclave with a polytetrafluoroethylene liner, the autoclave was sealed, heated at 200 °C, and reacted for 10 h. After the reaction was completed, the autoclave was cooled and the solid product in the reaction solution was centrifuged to collect 180 g black Fe 3 O 4 Nanoparticles, average particle size 90 nm, specific surface area 36m 2 / g.
[0024] Examples 1-6 of the present invention all use Fe prepared in Blank Example 1. 3 O 4 Preparation of immobilized enzymes using nanoparticles.
[0025] Example 1 Immobilization of protease on magnetic chitosan microspheres
[0026] 500 g of chitosan powder was dissolved in 50 L of 0.1% acetic acid aqueous solution to obtain a 1.0% (w / v) chitosan solution. Then 1 kg of Fe 3 O 4 The obtained mixture was stirred at room temperature to remove bubbles, and then slowly dripped into an excess of 2 mol / L NaOH solution to form microspheres. After soaking in the NaOH solution for 10 h, the solid product was magnetically separated and recovered, washed with deionized water until neutral, and the microspheres were collected and soaked in a 0.5% (v / v) glutaraldehyde aqueous solution at 25 °C for 2 h. The solid product was magnetically separated and recovered, and the excess glutaraldehyde was washed with deionized water to obtain activated microspheres.
[0027] 50 g of activated microspheres were added to 10 L of 50 g / L alkaline protease aqueous solution, slowly shaken at room temperature for 2 h, and then placed in a refrigerator at 4 °C for 16 h. The microspheres were separated by a magnet, washed repeatedly with 0 °C ice-cold 0.1 M acetic acid-sodium acetate buffer (pH 9.0), and freeze-dried in a vacuum to obtain chitosan-immobilized protease, referred to as immobilized enzyme, and the protease recovery rate and immobilized enzyme activity were determined.
[0028] Example 2 Immobilized protease on sodium alginate
[0029] 500 g of sodium alginate was dissolved in 25 L of distilled water to obtain a 2.0% (w / v) sodium alginate solution, to which Fe was added at a final concentration of 16 g / L. 3 O 4 Powder, stirred for 30 min. The mixed solution was heated to 80 °C under nitrogen protection and stirred for 1 h. Subsequently, ultrasonic dispersion was further performed for 20 min, 1250 g of alkaline protease was added to make the final concentration of alkaline protease in the mixed solution 50 g / L, mixed evenly and then atomized and sprayed into 10 L of 10 wt% CaCl 2 The solid product was recovered by magnetic separation, washed with distilled water, added to 5L of 0.5% glutaraldehyde aqueous solution, and cross-linked at room temperature for 1.5 h. The solid product was recovered by magnetic separation, washed with distilled water to remove excess glutaraldehyde, and placed in a refrigerator at 4°C for hardening. Vacuum freeze-drying was performed to obtain sodium alginate immobilized protease, referred to as immobilized enzyme, and the protease recovery rate and immobilized enzyme activity were determined.
[0030] Example 3 Nano-Fe 3 O 4 Loading immobilized protease 10 g Fe 3 O 4 The nanoparticles were dispersed in 1000 mL ultrapure water, the pH was adjusted to 8.0, 50 g of alkaline protease was added to make the final concentration of alkaline protease in the mixture 50 g / L, and the mixture was stirred and adsorbed for 20 min, then filtered and vacuum-frozen to obtain Fe 3 O 4 Immobilized protease, referred to as immobilized enzyme, was used to determine the protease recovery rate and immobilized enzyme activity.
[0031] Example 4 Polyethylene glycol modified nano-Fe 3 O 4 Loading immobilized protease The average molecular weight of polyethylene glycol is 1000, and it is dissolved in water to prepare a polyethylene glycol solution with a mass concentration of 0.8%.
[0032] 500g Fe 3 O 4 The nanoparticles were dispersed in 10 L of the polyethylene glycol solution prepared above, and the suspension was kept at 40°C with nitrogen for 20 minutes, then ultrasonicated at 19W, 40 kKz for 20 minutes, and the precipitate was collected by centrifugation and freeze-dried to obtain polyethylene glycol-modified nano-iron oxide. 500 g of polyethylene glycol / iron oxide nanoparticles were dispersed in 50 L of ultrapure water, pH was adjusted to 8.0, 2500 g of alkaline protease was added to make the final concentration of alkaline protease in the mixed solution 50 g / L, stirred and adsorbed for 20 minutes, then filtered, the nanoparticles were collected and freeze-dried to obtain nano-iron oxide immobilized protease, referred to as immobilized enzyme, and the protease recovery rate and immobilized enzyme activity were determined.
[0033] Example 5 Sodium alginate embedded polyethylene glycol modified nano-Fe 3 O 4 Loading immobilized protease The preparation steps of the immobilized enzyme in Example 5 include: Step 1: Repeat the experimental steps of Example 4 to prepare polyethylene glycol-modified nano-Fe 3 O 4 Loading immobilized protease; Step 2: Take the polyethylene glycol-modified nano-Fe prepared in step 1 3 O 4 500 g of immobilized protease was dispersed in 50 L of 2% sodium alginate aqueous solution, mixed evenly, and then sprayed with 10 L of 10 wt% CaCl 2The solid product was magnetically separated and recovered, washed with distilled water, added to 5L of 0.5% glutaraldehyde aqueous solution, and cross-linked at room temperature for 1.5 h. The solid product was magnetically separated and recovered, washed with distilled water, and vacuum freeze-dried to obtain sodium alginate-encapsulated polyethylene glycol-modified nano-Fe 3 O 4 The immobilized protease was loaded, referred to as immobilized enzyme, and the protease recovery rate and immobilized enzyme activity were determined.
[0034] Example 6 Sodium alginate embedded polyethylene glycol modified nano-Fe 3 O 4 Loading immobilized protease The preparation steps of the immobilized enzyme in Example 6 include: Step 1: Repeat the experimental steps of Example 4 to prepare polyethylene glycol-modified nano-Fe 3 O 4 Loading immobilized protease; Step 2: Take the polyethylene glycol-modified nano-Fe prepared in step 1 3 O 4 500 g of immobilized protease and 500 g of alkaline protease were dispersed in 50 L of 2% sodium alginate aqueous solution, mixed evenly, and then sprayed with 10 L of 10 wt% CaCl 2 The solid product was magnetically separated and recovered, washed with distilled water, added to 5L of 0.5% glutaraldehyde aqueous solution, and cross-linked at room temperature for 1.5 h. The solid product was magnetically separated and recovered, washed with distilled water, and vacuum freeze-dried to obtain sodium alginate-encapsulated ethylene glycol-modified nano-Fe 3 O 4 Loading of immobilized protease.
[0035] The enzyme activities of the immobilized enzymes prepared in Examples 1-6 were measured respectively, and the enzyme activity recovery rate in the preparation process of the immobilized enzyme was calculated according to the following formula: enzyme activity recovery rate (%) = (total enzyme activity of the immobilized enzyme / total enzyme activity of the free enzyme used) × 100%. Taking the immobilized enzyme prepared in Example 6 as an example, in the calculation process of its enzyme activity recovery rate, the free enzyme used includes two parts.
[0036] The enzyme activity and enzyme activity recovery rate of the immobilized enzymes prepared in Examples 1-6 were tested respectively. The test results are shown in Table 1.
[0037] Table 1 .
[0038] The activity and recovery rate of immobilized proteases obtained by different immobilization methods are shown in Table 1. The recovery rate of enzyme activity in Table 1 reflects, on the one hand, the amount of protease loaded by the carrier from the solution, and on the other hand, the activity of the enzyme after immobilization. It can be seen from Table 1 that: 1) The surface immobilization methods of Example 1 and Example 4 have higher enzyme activity because the steric hindrance of the enzyme adsorbed on the carrier surface is small and the contact area between the enzyme adsorbed on the carrier surface and the casein substrate is large. However, because the surface area of the carrier is relatively small and the enzyme adsorption capacity is limited, the enzyme activity recovery rate is not high (<10%).
[0039] 2) Example 3 Nano-ferroferric oxide has a high pore size ratio and a large specific surface area, and the enzyme activity recovery rate is significantly increased (35.62%), but the enzyme activity is reduced due to steric hindrance. This is because the pores of nano-ferroferric oxide adsorb proteases, and the contact reaction between the protease and the casein substrate is divided into the following two situations: ① The casein substrate enters the pores of nano-ferroferric oxide and contacts the protease; ② The protease diffuses out of the pores of nano-ferroferric oxide into the solution and contacts the casein substrate. Both situations have steric hindrance.
[0040] 3) In Example 2, the group of ferric oxide and free protease embedded in sodium alginate had the highest enzyme activity recovery rate, reaching 92.32%. Due to the increase in mass transfer resistance of the physical embedding substrate, the enzyme activity dropped to 16000 (U / g). In addition, the presence of protease and Fe 3 O 4 The problem of uneven embedding.
[0041] 4) Example 5: First, the enzyme is fixed on the nano-Fe 3 O 4 The surface was then encapsulated with sodium alginate, which effectively solved the problems of uneven encapsulation and enzyme stability, but some enzyme activity was sacrificed due to the complex mass transfer.
[0042] 5) Example 6: Fe 3 O 4 The surface-immobilized protease and free enzyme are co-encapsulated in the large-pore sodium alginate microspheres, which solves the problem of low enzyme activity recovery rate. At the same time, the presence of some free enzymes inside the sodium alginate microspheres improves mass transfer and maintains high activity. At the same time, the mechanical collision tolerance of the flexible immobilized enzyme is enhanced and it is not easy to break. 3 O 4 The protease fixed on the surface is not easy to fall off and can maintain stable catalysis for a long time, which enables the repeated catalytic use of enzymes in complex heterogeneous systems and greatly improves the production economy.
[0043] Application Example 1: Using the present invention Figure 1-Figure 2The device of the structure is used for bio-oil production, and the device includes a stirred reactor 1 of a kettle structure, wherein an overflow port 4 is provided at the upper end of the stirred reactor 1, and a lower discharge port 5 is provided at the bottom. A heat exchange jacket for heating the stirred reactor 1 is provided on the outer side of the stirred reactor 1, and a heat exchange fluid is passed into the heat exchange jacket. An annular magnet 3 is provided on the outer side of the heat exchange jacket, and the annular magnet 3 is connected to a power supply through a wire. The stirred reactor 1 and the heat exchange jacket are both made of non-magnetic stainless steel. A stirring paddle 2 is provided at the center of the stirred reactor 1, and the upper end of the stirring paddle 2 passes through the top of the stirred reactor 1 and is fixedly connected to the motor. Three groups of stirring blades 201 are provided at intervals from top to bottom at the lower end of the stirring paddle 2, and each group of stirring blades 201 includes three stirring blades 201 evenly spaced along the circumferential direction, and the edges of the stirring blades 201 are smooth arc-shaped edges. The stirring blades 201 are inclined relative to the horizontal plane, and the stirring blades 201 are also evenly distributed with liquid permeable holes ( Figure 2 The stirring paddle 2 and the stirring blade 201 are both made of polytetrafluoroethylene.
[0044] In addition Figure 2 In the figure, the end of the stirring blade 201 close to the stirring blade 2 is recorded as the inner end, and the end of the stirring blade 201 away from the stirring blade 2 is recorded as the outer end. The blade width of the inner end of the stirring blade 201 is greater than the blade width of the outer end of the stirring blade 201. The inner end of the stirring blade 201 is widened to increase the liquid displacement of the root blade and improve the stability of the stirring blade 201 during stirring.
[0045] Application Example 1 of the present invention Figure 1-Figure 2 The device of the structure is used to produce oil from biomass, and the specific process steps are as follows: 1) The shelled camellia seeds were mechanically crushed and passed through a 100-mesh sieve. 50 kg of camellia seed powder was dispersed in 350 kg of soft water in a stirred reactor. The mixed solution in the stirred reactor 1 was heated to 60°C and then kept warm. NaOH solution was added dropwise to the mixed solution to adjust the pH to 9.0. 2) Add 400 g of immobilized enzyme to the mixed solution of step 1), and carry out hydrolysis reaction at 60° C. for 4 h at a stirring speed of 200 rpm. Then terminate the reaction, stop stirring, and let the mixture stand to separate the oil and water into an upper oil phase and a lower water phase. The immobilized enzyme is enriched in the lower water phase. Water is introduced into the bottom of the stirred reactor 1 to collect the upper oil from the overflow port. The collected oil product is dehydrated and weighed to calculate the oil yield obtained by hydrolysis extraction of camellia seeds, and the unit is g oil / 100 g camellia seeds.
[0046] 3) Then restart the stirring to evenly disperse the immobilized enzyme in the aqueous phase, energize the annular magnet on the outside of the side of the stirred reactor to adsorb the immobilized enzyme on the inner wall of the side of the stirred reactor, and discharge the mixed liquid containing the slurry from the lower discharge port at the bottom of the stirred reactor. Rinse the inside of the stirred reactor with clean water, and then repeat the cycle of the immobilized enzyme adsorbed on the inner wall of the side of the stirred reactor.
[0047] 4) Add new camellia seed powder to the stirred reactor, and carry out the next batch of hydrolysis reaction according to the operating process of steps 1)-3), and cut off the power of the annular magnet on the outside of the side of the stirred reactor to allow the immobilized enzyme to be repeatedly dispersed in the reaction liquid in the stirred reactor. The hydrolysis reaction time for each batch is 4 hours. The cyclic experiment is carried out to test the experimental results under the cyclic application of the immobilized enzyme.
[0048] According to the experimental process of steps 1)-4) of Example 1, when the immobilized enzymes in the hydrolysis reaction are respectively prepared by Examples 1-6, the oil yields and enzyme half-life calculation results of the immobilized enzymes at different times of use are summarized in Table 2.
[0049] Table 2 .
[0050] In addition, according to the experimental results in Table 2, a fitting curve equation for the hydrolysis reaction using the immobilized enzyme prepared in each embodiment was established. The fitting curve equation describes the relationship between the number of times the immobilized enzyme is used and the oil yield. In the fitting curve equation, the oil yield is the ordinate, and the total hydrolysis time under the number of times the immobilized enzyme is used is the abscissa. The total hydrolysis time when the immobilized enzyme is used once is 4 h, the total hydrolysis time when the immobilized enzyme is used twice is 8 h, the total hydrolysis time when the immobilized enzyme is used three times is 12 h, and so on.
[0051] According to the above experimental conditions, when the immobilized enzymes prepared in Examples 1 to 6 were used in the hydrolysis reaction, the corresponding results of the oil yield with the total hydrolysis time under the number of times the immobilized enzymes were used are summarized in Figure 3 In the equation, the corresponding fitting curve equations are as follows: 1) When the immobilized enzyme prepared in Example 1 was used, the fitting curve equation established was y=49.223e -0.035x , correlation coefficient R 2 =0.9954.
[0052] 2) When the immobilized enzyme prepared in Example 2 was used, the fitting curve equation established was y=49.215e -0.029x , correlation coefficient R 2 =0.9807.
[0053] 3) When the immobilized enzyme prepared in Example 3 was used, the fitting curve equation established was y=47.952e -0.045x , correlation coefficient R 2 =0.991.
[0054] 4) When the immobilized enzyme prepared in Example 4 was used, the fitting curve equation established was y=50.607e -0.032x , correlation coefficient R 2 =0.9918.
[0055] 5) When the immobilized enzyme prepared in Example 5 was used, the fitting curve equation established was y=42.625e -0.018x , correlation coefficient R 2 =0.9988.
[0056] 6) When the immobilized enzyme prepared in Example 1 was used, the fitting curve equation established was y=49.973e -0.014x , correlation coefficient R 2 =0.9947.
[0057] The calculation process of the half-life in Table 2 is to use the established fitting curve equation to calculate the hydrolysis time required when the oil yield reaches 50% of the oil yield when the immobilized enzyme is used for the first time, that is, the hydrolysis time is 4 hours, and record it as the calculated half-life result.
[0058] From the experimental results in Table 2, we can see the following conclusions: 1) After the first batch of hydrolysis reactions of the immobilized enzymes prepared in Examples 1 to 6, the oil yield was very high, about 40 g / 100 g of tea seeds.
[0059] 2) The immobilized enzymes in Examples 2 and 4 had the best activity and the first batch of hydrolyzed oil yield was the highest. However, during repeated use, the instability of the enzyme immobilized on the rigid carrier was prominent. For example, the Fe 3 O 4 The half-life of the immobilized enzyme adsorbed and loaded was only 15.4 h, indicating that the heterogeneous slurry-residue mixed system had violent collisions during the reaction, the carrier was easily broken, and the internal enzyme was easily separated from the carrier and the stability was poor. 3 O 4 The stability of the loaded immobilized enzyme is slightly better, with a half-life of 21.7 h. The stability of the immobilized enzyme embedded in the sodium alginate magnetic microspheres in Example 2 is higher, with a half-life of 23.9 h, which may be related to the flexibility and collision resistance of the hydrogel surface. However, due to the long-term reaction and collision of the physically embedded protease, it has gradually desorbed and diffused from the gap into the solution, and its stability is still insufficient.
[0060] 3) Example 6 First, ethylene glycol-modified nano-Fe3 O 4 The alkaline protease was immobilized on the surface and then embedded into sodium alginate together with some free proteases. This not only solved the problem of enzyme activity, but also greatly improved the stability of the immobilized enzyme. The half-life was 49.51h and it could be used continuously for 10 batches while maintaining relatively high activity.
[0061] In addition, the enzymatic activity of the sodium alginate immobilized protease prepared in Example 2 in Table 1 is relatively low, which is the result of the enzyme activity test system in accordance with the GB / T 23527-2009 method, because the mass transfer effect is affected after sodium alginate embedding. However, what is tested in Table 2 is the reaction result in the system where the immobilized enzyme actually catalyzes the hydrolysis reaction, which reflects the average activity of the immobilized enzyme. The high activity proves that the immobilized enzyme has good stability and slow inactivation, so the average catalytic effect is good.
[0062] Application Example 2: Bio-oil production was performed using the immobilized enzymes prepared in Examples 1 to 6, respectively. The specific process steps were repeated in Application Example 1, except that the hydrolysis reaction was performed using an existing conventional reactor. For conventional reactors, after each hydrolysis reaction, a magnet was manually inserted into the reaction mixture to recover the immobilized enzyme for the next batch of hydrolysis reactions.
[0063] When the immobilized enzymes prepared in Examples 1 to 6 were used as the immobilized enzymes in the hydrolysis reaction of Application Example 2, the oil yields and enzyme half-life calculation results of the immobilized enzymes at different times of use are summarized in Table 3.
[0064] Table 3 .
[0065] When the immobilized enzymes prepared in Examples 1 to 6 are used as the immobilized enzymes in the hydrolysis reaction of Application Example 2 of the present invention, the corresponding results of the oil yield as a function of the total hydrolysis time under the number of times the immobilized enzymes are used are summarized in Figure 4 middle.
[0066] In the results of Table 3 obtained by Application Example 2 of the present invention, the calculation method of the half-life is the same as that in Application Example 1.
[0067] According to Table 2 of Application Example 1, by comparing the results with those of Table 3 of Application Example 2, it can be seen that the stirring blades of the reactor also have a great influence on the enzyme-catalyzed hydrolysis reaction. The use stability of the immobilized enzyme can be further greatly improved by using the special reactor of the present invention.
[0068] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.
Claims
1. A method for preparing an immobilized enzyme, characterized in that The polyethylene glycol-modified Fe3O4 nanoparticles are used as a matrix, and the matrix and the first part of free protease are stirred in ultrapure water to fully adsorb the free protease on the matrix, and then filtered, the nanoparticles are collected and freeze-dried to obtain polyethylene glycol-modified nano-Fe3O4 loaded immobilized protease, which is then dispersed in a sodium alginate aqueous solution together with the second part of free protease and mixed evenly to coat the sodium alginate on the outer layer, and then sequentially passed through Ca 2+ The two-step process of ion hardening and glutaraldehyde cross-linking reaction causes the sodium alginate in the outer layer to react to form a mesh-shaped large-pore gel microsphere, and the polyethylene glycol-modified nano-Fe3O4-loaded immobilized protease and the second part of free protease are co-embedded in the gel microsphere. Finally, the microsphere complex encapsulating the second part of free protease and the polyethylene glycol-modified nano-Fe3O4-loaded immobilized protease is prepared by washing with distilled water and vacuum freeze-drying. The preparation is completed.
2. The method for preparing an immobilized enzyme according to claim 1, characterized in that The preparation method of the polyethylene glycol-modified nano-Fe3O4-loaded immobilized protease specifically comprises the following steps: Step 1: Fe3O4 nanoparticles are dispersed in a polyethylene glycol aqueous solution, and the suspension is ultrasonically dispersed at 30-50°C for 10-30 minutes under nitrogen gas flow, and the precipitate is collected by centrifugation and freeze-dried to obtain polyethylene glycol-modified nano-iron oxide; wherein the molecular weight of the polyethylene glycol is 500-2000, and the mass ratio of the Fe3O4 nanoparticles to the polyethylene glycol is 1:1.5-1.8; Step 2: The polyethylene glycol-modified nano-iron oxide obtained in step 1 and the first part of free protease are dispersed in ultrapure water at a mass ratio of 4-8:1, and adsorbed with stirring for 10-30 minutes under the condition of adjusting the pH to 7.5-8.5, and then filtered, the nanoparticles are collected and freeze-dried to obtain the polyethylene glycol-modified nano-Fe3O4-loaded immobilized protease.
3. The method for preparing an immobilized enzyme according to claim 1, characterized in that The method for preparing the microsphere complex encapsulating the second part of free protease and the polyethylene glycol-modified nano-Fe3O4 loaded with immobilized protease specifically comprises the following steps: S1: The polyethylene glycol-modified nano-Fe3O4 loaded immobilized protease and the second part of free protease are dispersed in a sodium alginate aqueous solution at a mass ratio of 0.8-1.2:1, wherein the mass ratio of the polyethylene glycol-modified nano-Fe3O4 loaded immobilized protease to sodium alginate is 1:1.5-3; S2: The mixed solution obtained in step S1 is sprayed into Ca 2+ After hardening treatment in an ionic aqueous solution at 2-5°C for 0.5-2h, magnetic immobilized microspheres are obtained, which are washed with distilled water; wherein the sodium alginate in step S1 and the Ca in step S2 2+ The mass ratio of ions is 1:0.3-0.5; S3: The magnetic immobilized microspheres obtained in step S2 are immersed in a glutaraldehyde aqueous solution with a mass dispersion of 0.1-1%, and a cross-linking reaction is carried out at room temperature for 1-2 hours. The precipitate is then separated by centrifugation, washed with distilled water to remove excess glutaraldehyde, and then vacuum freeze-dried to complete the preparation.
4. An immobilized enzyme prepared by the method according to any one of claims 1 to 3.
5. A bio-oil production method based on reusable immobilized enzyme, characterized in that The shelled camellia seed powder and soft water are added to a stirred reactor, the pH of the reaction solution is adjusted to alkaline, the immobilized enzyme according to claim 4 is added, and a stirring hydrolysis reaction is carried out; after the reaction is completed, the stirring is stopped, the mixture is allowed to stand to separate the oil and water layers, the upper layer of fat is discharged, and the product oil is obtained after dehydration and drying; then the stirring is restarted, the annular magnet on the outer side of the stirred reactor is energized, the immobilized enzyme is adsorbed on the inner wall of the side of the stirred reactor, the mixed solution containing the pulp residue is discharged from the lower discharge port at the bottom of the stirred reactor, the inside of the stirred reactor is rinsed with clean water, and the shelled camellia seed powder and soft water are added again to carry out the next batch of hydrolysis reaction, so as to realize the reuse of the immobilized enzyme.
6. A bio-oil production method based on reusable immobilized enzyme according to claim 5, characterized in that The mass ratio of the shelled camellia seed powder to soft water for hydrolysis reaction is 1:4-10, and the mass of the immobilized enzyme is 0.5-1% of the mass of the shelled camellia seed powder.
7. A bio-oil production method based on reusable immobilized enzyme as claimed in claim 5, characterized in that The reaction temperature for the hydrolysis reaction is 50-70°C, the reaction time is 3-5h, and the stirring speed is 150-300rpm.
8. A bio-oil production method based on reusable immobilized enzymes as claimed in claim 5, characterized in that The pH of the reaction solution was adjusted to 8.5-9.
5.
9. The device used in the bio-oil production method according to claim 5, characterized in that The invention comprises a stirred reactor (1) of a kettle structure, wherein an overflow port (4) is arranged at the upper end of the stirred reactor (1), and a lower discharge port (5) is arranged at the bottom. A heat exchange jacket for heating the stirred reactor (1) is arranged on the outer side of the stirred reactor (1), and a heat exchange fluid is passed into the heat exchange jacket. An annular magnet (3) is arranged on the outer side of the side of the heat exchange jacket, and the annular magnet (3) is connected to a power supply through a wire. The stirred reactor (1) and the heat exchange jacket are both made of non-magnetic stainless steel. A stirring paddle (2) is arranged at the center of the stirred reactor (1), and the upper end of the stirring paddle (2) passes through the top of the stirred reactor (1) and is fixedly connected to a motor. A plurality of stirring blades (201) are arranged at intervals from top to bottom at the lower end of the stirring paddle (2), and the edges of the stirring blades (201) are smooth arc-shaped edges. The stirring blades (201) are arranged to be inclined relative to a horizontal plane, and liquid permeable holes are evenly distributed on the stirring blades (201). The stirring paddle (2) and the stirring blades (201) are both made of plastic.
10. The device according to claim 9, characterized in that The stirring paddle (2) and the stirring blade (201) are both made of polytetrafluoroethylene.
Citation Information
Patent Citations
Magnetic nano immobilized enzyme catalysis production method of soya isoflavone
CN101532039A
In-situ continuous separating device for magnetic medium particles
CN102133555A
Method for preparing corn protein active peptide by using composite carrier immobilized double enzymes
CN103352064A
Magnetic thermosensitive liposome nano-gold comopound, preparation method and application
CN103768600A
Preparation method of magnetic porous chitosan immobilized enzyme carrier with rocking arm structure
CN104046611A